Effects of isometric handgrip training on cardiac autonomic profile: A systematic review and meta-analysis study - Farah, Breno Q.; Christofaro, Diego G. D. [UNESP]; Correia, Marilia A.; Oliveira, Crystian B. [UNESP]; Parmenter, Belinda J.; Ritti-Dias, Raphael M. (Wiley, 2020)
Meta-analyses have shown that isometric handgrip training reduces blood pressure in normotensive and hypertensive subjects. However, the effects on cardiac autonomic modulation are still controversial. Thus, the aim of this systematic review and meta-analysis was to analyse the effects of isometric handgrip training on cardiac autonomic modulation in normotensive and hypertensive subjects. For this, Medline, Cinhal, Embase, Spordiscus and PEdro were searched for relevant studies published until December 2018. Randomized controlled trials investigating the effect of isometric handgrip training on heart rate variability parameters were considered eligible. Parameters were obtained in time (standard deviation of all the RR intervals-SDNN, root mean square of successive differences between the normal adjacent RR intervals-RMSSD and the percentage of adjacent intervals with more than 50 ms-PNN50) and frequency domain (low frequency-LF, high frequency-HF and sympathovagal balance-LF/HF). Mean difference (MD) and 95% confidence interval (95% CI) were calculated using an inverse variance method with a random effects model. Seven trials were included in the systematic review and meta-analysis, totalling 86 participants. No significant effect was observed in heart rate variability parameters after isometric handgrip training (4 trials to SDNN: MD = −1.44 ms and 95% CI = −8.02, 5.14 ms; RMSSD: MD = −1.48 ms and 95% CI = −9.41, 6.45 ms; PNN50: MD = 0.85% and 95% CI = −1.10, 2.81%; 7 trials to LF: −0.17 n.u. and 95% CI = −6.32, 5.98 n.u.; HF: MD = 0.17 n.u. and 95% CI = −5.97, 6.30 n.u.; and LF/HF: MD = 0.13 and 95% CI = −0.34, 0.59). In conclusion, current literature indicates that isometric handgrip training does not improve heart rate variability.
Keywords: autonomic nervous system; blood pressure; exercise; heart rate; hypertension